2013
DOI: 10.7860/jcdr/2013/5370.2946
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serum Osteocalcin with the Bone Mineral Density in Post Menopausal Women

Abstract: Background: The markers of bone remodelling, such as serum osteocalcin, may be used to assess osteoporosis and to predict the fracture risk in elderly persons, especially in women. The bone mineral density which reflects the bone mass and strength, also predicts osteoporotic related hip fractures. So, this work highlights the association between the bone turnover and the bone mass and strength. Aim:To assess the association between the biochemical markers of bone remodeling and osteocalcin with the bone minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 8 publications
5
22
0
Order By: Relevance
“…Therefore, in patients with osteoporosis, H‐type hypertension can lead to the activity of osteoblasts increasing. These results were consistent with those of Kalaiselvi. In the clinic, we could evaluate bone synthesis in patients with osteoporosis by detecting the serum levels of PINP and OC.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in patients with osteoporosis, H‐type hypertension can lead to the activity of osteoblasts increasing. These results were consistent with those of Kalaiselvi. In the clinic, we could evaluate bone synthesis in patients with osteoporosis by detecting the serum levels of PINP and OC.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, studies have shown that long-term estrogen deficiency increased both bone resorption and bone formation markers in postmenopausal women, suggestive of enhanced bone turnover with increased net bone loss [ 88 , 89 , 90 , 91 ]. Estrogen deficiency increases renal calcium excretion while decreasing intestinal calcium absorption [ 10 ], and the resultant fall in calcium levels can activate various bone resorption mechanisms that include PTH, osteocalcin, OPG, and the RANK/RANKL system [ 91 , 92 , 93 , 94 , 95 ]. These bone resorption markers are, therefore, found in the blood in higher concentrations in osteoporosis.…”
Section: Postmenopausal Osteoporosis: a Silent Diseasementioning
confidence: 99%
“…The diminished bone density associated with this disease is a major risk factor for fractures, especially fractures of the hip, spine, and wrist. Osteoporosis is primarily a consequence of physiological bone loss, but it can be secondary to certain medical treatment (e.g., glucocorticoid (GC), anticonvulsants, cytotoxic drugs, excessive thyroxine, heparin, aluminum-contained antacids, lithium, and tamoxifen) or diseases, such as rheumatoid arthritis, diabetes, chronic kidneys, and primary hyperparathyroidism [68]. …”
Section: Introductionmentioning
confidence: 99%